Trade balance and j _curve phenomenon in Malaysia - Rizaudin Sahlan,; Hussein Abdullh,; Mohd Ridhuan Boss Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2008)
This paper examines the effects of real exchange rate changes on the trade balance of Malaysia and her trading partners (Japan, Singapore, United Kingdom, and United State of America). The response of the trade balance through time then form the famous J Shape. Using yearly data from 1970-2003 and co integration analysis, we found that there is avidence of J-curve at least in the cases of USA and Japan.